Diversion in the settlement of the criminal act of disposal of infants - Sanusi, Sanusi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The rise of child promiscuity has resulted in children becoming pregnant out of wedlock and then giving birth. This act is a criminal offense of child neglect. The perpetrator of child neglect who is under 18 years of age is of course handled differently from adults. This research aims to find out how the reasons for dumping babies and what sanctions will be given and the form of diversion carried out by the police. This research method uses empirical juridical, where the actions committed by the perpetrators (parents) of baby dumping under the age of 18, are not included in the Child Protection Law, so they must be held accountable and the settlement must use diversion as a form of protection for living babies. The results of this study indicate that child offenders who dump their babies have violated Article 78 B of Law Number 35 of 2014 concerning Amendments to Law Number 11 of 2012 concerning Child Protection, and can be subject to sanctions for babies dumped as babies. The perpetrator is married and is obliged to take care of the discarded baby until adulthood. The perpetrator is still a child and the child born also needs protection and care, so the settlement of the case is through diversion by bringing together the perpetrator's parents, community, and religious leaders. and mediated by the police.